Analyzing Factors Influencing Flow Experience in Battle Royale Games: A Case Study of Free Fire MAX - Fatih, Farrel Andhika; Saputra, Edi; Bintana, Rizqa Raaiqa (Universitas Multimedia Nusantara, 2025)
The rapid growth of the mobile gaming industry, especially within the Battle Royale genre, has reshaped player engagement and competition. Free Fire MAX stands out by combining immersive gameplay with narrative driven elements that sustain long term involvement. This study investigates the influence of Game Design Factors (GDF) on players’ Flow Experience using quantitative analysis. Eleven factors Game Goals, Game Mechanism, Interaction, Freedom, Game Fantasy, Narrative, Sensation, Game Value, Challenges, Sociality, and Mystery were examined. Results show that Narrative, Challenges, and Mystery significantly affect Flow (Sig < 0.05), while others have no substantial impact. The narrative dimension, reinforced through collaboration based storytelling such as themed skins and crossover events, enhances emotional engagement. The challenge factor promotes Flow through balanced difficulty and adaptive gameplay, while the mystery element stimulates curiosity through hidden rewards and unpredictable events. Gender based analysis revealed no significant difference in Flow between male and female players, indicating that psychological immersion transcends gender. These findings support Csikszentmihalyi’s Flow Theory and Shi and Shih’s (2015) Game Design Factors model, emphasizing that engaging narratives, balanced challenges, and mystery driven discovery are key to sustaining player immersion in competitive mobile gaming.